Altered White Matter Integrity in Smokers Is Associated with Smoking Cessation Outcomes - Huang, Peiyu; Shen, Zhujing; Wang, Chao; Qian, Wei; Zhang, Huan; Yang, Yihong; Zhang, Minming (Frontiers in Human Neuroscience, 2017)
Smoking is a significant cause of preventable mortality worldwide. Understanding the neural mechanisms of nicotine addiction and smoking cessation may provide effective targets for developing treatment strategies. In the present study, we explored whether smokers have white matter alterations and whether these alterations are related to cessation outcomes and smoking behaviors. Sixty-six smokers and thirty-seven healthy nonsmokers were enrolled. The participants underwent magnetic resonance imaging scans and smoking-related behavioral assessments. After a 12-week treatment with varenicline, 28 smokers succeeded in quitting smoking and 38 failed. Diffusion parameter maps were compared among the nonsmokers, further quitters and relapsers to identify white matter differences. We found that the further relapsers had significantly lower fractional anisotropy (FA) in the orbitofrontal area than nonsmokers, and higher FA in the cerebellum than nonsmokers and further quitters. The further quitters had significantly lower FA in the postcentral gyrus compared to nonsmokers and further relapsers. Compared to nonsmokers, pooled smokers had lower FA in bilateral orbitofrontal gyrus and left superior frontal gyrus. In addition, regression analysis showed that the left orbitofrontal FA was correlated with smoking-relevant behaviors. These results suggest that white matter alterations in smokers may contribute to the formation of aberrant brain circuits underlying smoking behaviors and are associated with further smoking cessation outcomes.